(3aUd aj JNWjW GdSGYGJ GdReGfjI aj cd bHI Ch aj bHI jSJYed dgGs - (3GdaVd Hf MGJe GdfjQjRj, CHh GdYHGS,J (B310 (3g` s
(3ChdgG (B:s
(3jNW ai bGYOI GdbHI OGFQI CYXe eGjchf cgjFI bGYOI (B( (3CHLO (B) (3heQcRgG fbWI (B( 5) s
(3BNQgG (B:s
(3hdGjRGd jaUd Pdc ai JbHjH GdbHI ai MGFWgG hai CQVgG GdJi gi OGFQI (B( (3CHLO (B) (3MJi jSJJe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B144(3H (B- (3U(B145(3Hs
(3HgG Tcd gfOSis
(3HgG fXGe GdJYbjHIs
(3cJH Hbde eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs